Outcome of Hemorrhoidectomy with the Ligasure in Comparison with the Traditional open Method - Rahman, Fiaz -Ur-; Amin, Arshad; Nisar, Shahid; Hussaind, Musarat (Journal of Gandhara Medical and Dental Science, 2017)
OBJECTIVE To compare the operative time and outcomes of Ligasure hemorrhoidectomy with that of the traditional open hemorrhoidectomy. METHODOLOGY A total of 49 patients were included in this study. Out of which 24 were in the Ligasure group and 25 in the open group. The main objective or the primary variable was to assess the operative time for the excision of a single hemorrhoidal lesion, the need for morphine, for post operative pain relief and any other complications such as preoperative bleeding and the time to return to work. The data like age, sex, type of Haemorrhoidectomy, type of complicating etc. were recorded in already prepared proforma. The data was analysed through computer program SPSS10. RESULTS The demographic data were comparable between the two groups. The time spent in excision of a solitary hemorrhoidal lesion was significantly shorter in the Ligasure group compared to the open group (8.25 min Vs 16.75 min ) and this difference was found to be statistically significant (p<0.001). Operative bleeding was also significantly lower than the open method of Haemorrhoidectony. Other parameters like post operative pain, opioid requirement, urinary retention and chronic complications like anal stenosis and gas incontinence were not significant. There was no difference in the period of convalescence and return to work between the two groups. CONCLUSION Hemorrhoidectomy with the Ligasure entails a shorter surgical time and could be associated with a lesser pain besides being safer.